Implikasi Marketing Mix dan Citra Sekolah terhadap Keputusan Orang Tua Memilih Sekolah Anak - Putra, Aldi Permana; Yetri, Yetri; Ayu, Sovia Mas (Tapis: Jurnal Penelitian Ilmiah, 2023)
Marketing mix is a stimulus given by the school to parents to influence parents' decisions in choosing a school. While school’s brand image is an additional stimulus that can strengthen parents' decisions in choosing schools. This study aims to see the influence of education services and school’s brand image in influencing parents' decisions to choose schools. This study is associative quantitative research with a sample of 21 parents of Junior High School Muhammadiyah Metro Pusat students. This study used questionnaires as a data collection method with statement items totalling 51 questions. Researchers completed validity tests, reliability tests, classification assumption tests and hypothesis tests. The results of the multiple linear regression test Marketing mix and School’s Brand Image Variable have positive value and have a partial effect on the decision to choose a school. The results of the f-test have concluded that the Marketing Mix and School’s Brand Image together affect the decision to choose a school.